PENGARUH PELATIHAN STAF KEUANGAN, PEMANFAATAN TEKNOLOGI INFORMASI, KOMITMEN ORGANISASI, SISTEM PENGENDALIAN INTERN, PEMAHAMAN STANDAR AKUNTANSI PEMERINTAH DAN AUDIT INTERNAL TERHADAP KUALITAS INFORMASI LAPORAN KEUANGAN (Studi Empiris Pada Organisasi Perangkat Daerah Kota Dumai) - Zuhri, Alif Khakam; Indrawati, Novita; Putra, Adhitya Agri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
Utilization of information technology, organizational commitment, internal control system, understanding of Government Accounting Standards and internal audit on the quality of financial statement information. Respoden in this research is 34 Organization of Regional Device (OPD) Dumai City. data processing methods used in this study is multiple regression analysis (multiple regression analysis) The number of this study was 136 respondents. The results of this study indicate that the Training of Finance Staff, Utilization of information technology, Organizational Commitment, Understanding Government Accounting Standards have a significant effect on the quality of Information financial statements, while the Internal Control system, Internal Audit has no significant effect on the quality of Financial statement informationKeywords : Training of Finance Staff, Utilization of Information Technology, Organizational Commitment, Internal Control System, Understanding of Government Accounting Standards, Internal Audit, Financial Information Quality of Financial Statement